Intuitionistic Fuzzy DEMATEL for Municipal Solid Waste Treatment Technologies - Zulkifli, Norsyahida; Abdullah, Lazim (International Journal of Engineering and Technology, 2018)
Nowadays municipal solid waste (MSW) has gained attention in Malaysia. It is an unresolved issue since MSW management system applies improper and unsustainable MSW treatment technologies. According to the rapid urbanization, MSW is outstripping generated and this situation could affect the environmental, health and safety of the citizens. Thus, this study aims to visualise the most viable MSW treatment using decision making trial and evaluation laboratory (DEMATEL).Â Intuitionistic fuzzy (IF) sets is applied in linguistic scales of DEMATEL to deal with the linguistic imprecision and vagueness of the human judgment. Six alternatives of waste treatment technologies were identified and three experts were invited to provide linguistic evaluation in this case study. The linguistic evaluations were then analyzed using the five-step computational of intuitionistic fuzzy DEMATEL (IF-DEMATEL). The result shows anaerobic digestion as the most sustainable MSW treatment in Malaysia.Â Â